Pulse rate during running 5 laps: comparative study before and after dehydration? - Apriandi, Dirzal; Salacup, Vince Louisse D.; Butali, Reygan A.; Cadiente, Derick Sam A.; Ardian, Roy; Septianto, Irvan; Azrina, Jihan (Universitas Tanjungpura, 2023)
Background and Study Aim. Dehydration is a condition where there is a lack of fluid in the body, accompanied by disturbances in the body's metabolic processes. This study aims to prove the effect of dehydration on 5 lap running by comparing the pulse rate before and after dehydration.Materials and Methods. This study used an experimental method. The population in this research is Tanjungpura University sports students. Purposive sampling technique so that a sample of 19 students was obtained. The sample consists of 4 women and 15 men. In the research, the implementation procedure will be to measure 2000 meter running performance before and after losing fluid, weighing body weight to precision ounces. Analysis was assisted using SPSS 26.Results. The results of the analysis showed a significance value of 0.000 <0.05, which is a significant difference between the pulse rate before and after dehydration when running 5 laps. The pulse rate after dehydration tended to be higher, indicating an increased cardiac workload during physical activity.Conclusions. This study concludes that dehydration has a direct influence on pulse rate when running 5 laps. The existence of this difference highlights the importance of maintaining an optimal hydration state in supporting a healthy cardiovascular response during physical activity, particularly in high-intensity exercise such as running. These findings can be used as a basis for the development of more effective hydration strategies in the context of aerobic physical activity.